Scientific and technical aspects of yogurt fortification: A review - Hadi Hashemi Gahruie; Mohammad Hadi Eskandari; Gholamreza Mesbahi; Mohammad Amin Hanifpour (Food Science and Human Wellness, 2015)
Food fortification is one of the most important processes for improvement of the nutrients quality and quantity in food. It can be a very cost effective public health intervention. Due to the high consumption rate of dairy products such as yogurt, fortification of these products will effectively reduce or prevent diseases associated with nutritional deficiencies. The aim of this investigation is to study the technical aspects involved in production of different types of fortified yogurts and their role in disease prevention and correction of deficiencies. In this paper, firstly, fortification is defined and the main reasons behind carrying out this process are presented and then yogurt production process and a variety of minerals, vitamins, and functional ingredients which are used in the process are briefly discussed.